The effect of feed and water provision strategies on broiler breeder pullet performance and welfare - Weaver, Allison D.; Bielke, Lisa R.; Malheiros, Ramon D.; Orlowski, Sara K.; Pullin, Allison N. (Frontiers in Veterinary Science, 2025)
Feed restriction is common in the broiler breeder industry to optimize health and reproduction. However, this practice has been associated with increased drinking behavior, leading to water spillage, higher litter moisture, and footpad lesions. Consequently, parts of the industry have adopted water restriction protocols. This study aimed to evaluate how different combinations of feed and water restriction affected drinking behavior, welfare, and performance indicators in broiler breeder pullets. At 1 day of age, 960 Cobb 500 FF pullets (Gallus gallus domesticus) were randomly allocated to one of four treatments: skip-a-day feeding with ad libitum water (SAD + ADLIB), every-day feeding with ad libitum water (ED + ADLIB), skip-a-day feeding with 3 h daily water restriction (SAD + WR), and every-day feeding with 3 h daily water restriction (ED + WR). All data were analyzed with generalized linear or linear mixed effects models in R Studio. Drinking behavior was observed at 16 and 22 weeks at an hour after feeding (HAF), when water was turned off for SAD + WR and ED + WR (12:00), and when water access resumed for SAD + WR and ED + WR (14:30). The ED pullets displayed more drinker use at HAF at both ages (p = 0.014), while SAD treatments performed more drinker use at 12:00 (p < 0.0001) and 14:30 (p = 0.0028) at 22 weeks. The WR pullets displayed more drinker use than ADLIB pullets at HAF and 14:30 (p < 0.0001), while ADLIB pullets performed more drinker use at 12:00 (p = 0.008). Water use (g/bird) was higher in ED + ADLIB pullets at 16 and 22 weeks compared to SAD+ADLIB pullets (p = 0.042), but WR groups did not differ (p > 0.05). Litter moisture under drinker lines reflected water use patterns, with ED pens wetter at 16 weeks (p = 0.0011), but SAD pens unexpectedly had higher moisture at 22 weeks (p = 0.011). General pen area litter was wetter in SAD and ADLIB groups (p = 0.0036). Footpad scores did not differ among treatments (p > 0.05). Body weight and uniformity did not drive water use. Overall, feeding program significantly influenced water use and behavior. Compensatory drinking in WR birds may indicate a welfare concern. Future research should explore measures of satiety and hydration to better understand the behavioral and physiological impacts of water restriction.